PENGARUH PROFITABILITAS, LIKUIDITAS, SOLVABILITAS, KEBIJAKAN DEVIDEN DAN PERTUMBUHAN PENJUALAN TERHADAP HARGA SAHAM PADA PERUSAHAAN PERTAMBANGAN TAHUN 2014 – 2023 - Tika Sri Kinasih; Sugiarti; Faiz Rahman Siddiq (ITB AAS INDONESIA, 2025)
This study aims to prove the effect of profitability, liquidity, solvency, dividend policy, and sales growth on stock prices. The population of this study are mining companies listed on the Indonesia Stock Exchange (IDX) for the period 2014-2023. The sample of this study amounted to 110 samples obtained from 11 companies for 10 years with purposive sampling method. The analysis technique used focuses on multiple regression analysis using the SPSS application. The results of this study indicate that Profitability and Dividend Policy have a significant positive effect on Stock Prices, while Liquidity, Solvency, Sales Growth have no effect on Stock Prices. Keywords : Stock Price, Profitability, Liquidity, Solvency, Dividend Policy, Sales Growth